Genotypic and Phenotypic Predictors of the Magnitude of Response to Tenofovir Disoproxil Fumarate Treatment in Antiretroviral‐Experienced Patients - Michael D. Miller; Nicolas Margot; Biao Lu; Lijie Zhong; Shanshan Chen; Andrew Cheng; Michael Wulfsohn (2004)
Results from 2 placebo-controlled intensification trials of tenofovir disoproxil fumarate (DF) in treatmentexperienced human immunodeficiency type 1 (HIV-1)-infected patients (n = 332) were integrated to determine the effects of resistance at baseline on HIV-1 RNA response. In these trials, there was a high prevalence of HIV-1 resistance mutations, with 94% of patients having nucleoside-associated mutations and 71% having thymidine analogue-associated mutations (TAMs). Statistically significant HIV-1 RNA reductions associated with tenofovir DF treatment, relative to placebo (P < .001), were observed for patients without TAMs (n = 97) or for patients with 1–2 (n = 88) or ⩾3 TAMs (n = 147). Response to tenofovir DF was reduced among patients with HIV-1 with ⩾3 TAMs inclusive of either the M41L or L210W mutation (n = 86) or patients who had a preexisting K65R mutation (n = 6). Slightly increased treatment responses were observed when the M184V mutation was present. Phenotypic cutoffs were established at 1.4-fold and 4-fold, respectively, for the beginning of reduced response to tenofovir DF and for a strongly reduced response. The results from these controlled clinical trials provide guidance for the use of tenofovir DF for treatment-experienced patients.